2018
DOI: 10.1007/s00234-018-2016-2
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of futile recanalization in patients undergoing endovascular treatment in a multicenter clinical trial

Abstract: In IMS III, futile recanalization was common. Delay in endovascular treatment is the only modifiable risk factor. Additional strategies for non-modifiable risk factors-female gender and high NIHSS-need to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 26 publications
6
99
0
2
Order By: Relevance
“…Of the two included studies, predictors for futile recanalization were age, stroke severity, maneuver count, intracranial stenting, and duration of the procedure. Other factors such as baseline NIHSS score, lower initial posterior circulation Alberta stroke program early CT score, and onset to start of endovascular treatment time were also identified by previous literature 24,26) . Our study showed comparable rates of successful recanalization in patients with PCO thrombectomy to patients with ACO.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 83%
“…Of the two included studies, predictors for futile recanalization were age, stroke severity, maneuver count, intracranial stenting, and duration of the procedure. Other factors such as baseline NIHSS score, lower initial posterior circulation Alberta stroke program early CT score, and onset to start of endovascular treatment time were also identified by previous literature 24,26) . Our study showed comparable rates of successful recanalization in patients with PCO thrombectomy to patients with ACO.…”
Section: Advance Publication Journal Of Atherosclerosis and Thrombosismentioning
confidence: 83%
“…Some, however, might consider moderately severe disability requiring assistance to attend to bodily needs or to walk (mRS 4) an acceptable, non-futile outcome. From a societal and health economics point of view, given the logistic and economic impact of endovascular treatment, there is a need to reduce FR (2,4). Known predictors of FR include age, National Institute of Health Stroke Scale (NIHSS) (2,5), procedure time (6), and leukoaraiois (7).…”
Section: Introductionmentioning
confidence: 99%
“…Among previously functional patients, particularly radiological imaging signs of advanced or completed irreversible brain infarction and significant delays in presentation or transportation impede eligibility for treatment or impair efficacy . Even if provided timely and technically successful, therapeutic recanalization as a prerequisite for stroke recovery alone does not guarantee a favorable outcome . This clinically unsatisfactory situation calls for further research regarding the complex and intertwined neurobiological processes of ischemic stroke that lead to final tissue damage …”
mentioning
confidence: 99%
“…[4][5][6] Even if provided timely and technically successful, therapeutic recanalization as a prerequisite for stroke recovery alone does not guarantee a favorable outcome. [7][8][9] This clinically unsatisfactory situation calls for further research regarding the complex and intertwined neurobiological processes of ischemic stroke that lead to final tissue damage. 10 Experimental data suggest that immune cells and platelets contribute to the evolution of cerebral infarction.…”
mentioning
confidence: 99%